Investigation on the Accuracy of Existing Qibla Directions of the Mosques from Different Periods: A Case Study in Çorum City, Turkey - Veli İlçi; İbrahim Murat Ozulu; Ersoy Arslan; Reha Metin Alkan (Tehnički Vjesnik, 2018)
The main goal of this study is to introduce two different approaches (i.e. based on spherical trigonometric formula and using sun qibla time) that can be used to determine the qibla directions of the existing mosques were oriented with sufficient accuracy according to Islamic criteria. In order to do this, eight mosques which were constructed in different periods, 14th, 16th, 17th and 21st centuries in Çorum City, Turkey, were handled. The existing qibla directions of each mosque were calculated with spherical trigonometric formula and compared with the precisely calculated real qibla directions. The existing qibla directions of the same mosques were once more compared with the real qibla directions which were determined by using the qibla time calculated based on the location and the time of the measurement. The results show that the qibla directions of the recently built mosques were oriented to Kâ’ba with higher accuracy while the earlier with more deviations. However, the results show that all the deviations were at acceptable levels in terms of Islamic criteria.